Hungarian Monitoring, 9 January 1989 . [Magyar rádiófigyelő], 1989. január 9 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - USSR to revise emigration policy - Pope John Paul II makes favorable statement on the USSR and Eastern European states - "This reform is not that reform", Jan Fojtík talks about 1968 at a Party activists' meeting in Pilsen - Traders in secret Nazi files receive light punishment Domestic Affairs: - Hungarian-Israeli relations - "The leaders' mistakes must once again be borne by the people", said Imre Pozsgay at meeting in Kaposvár with representatives of social groups - Interview with Péter Várkonyi - Tough government's price policy - Alternative groups' petition defending conscientious objectors Külpolitika: - A SZU felülvizsgálja az emigrációval kapcsolatos politikáját - II. János Pál pápa kedvezően nyilatkozott a SZU-ról és a kelet-európai államokról - "Ez a reform nem az a reform" - Jan Fojtík egy pilseni pártaktíva értekezleten beszélt 1968-ról - A titkos náci iratok adás-vételének szereplői enyhe büntetést kaptak Belpolitika: - Magyar-izraeli kapcsolatok - "A vezetés hibáit megint a népnek kell megbűnhődnie" - Mondta POZSGAY Imre Kaposvárott, ahol társadalmi szervezetek képviselőivel találkozott - Várkonyi Péter interjú - A kormány kemény árpolitikája - Alternatív csoportok petíciója a fegyveres katonai szolgálatot megtagadók védelmében